1997
DOI: 10.1002/(sici)1096-8628(19970531)74:3<275::aid-ajmg7>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Anticipation in schizophrenia: Biology or bias?

Abstract: Anticipation is a genetic phenomenon wherein age of disease onset decreases and/ or severity increases in successive generations. Anticipation has been demonstrated for several neuropsychiatric disorders with expanding trinucleotide repeats recently identified as the underlying molecular mechanism. We report here the results of an analysis of anticipation performed with multiplex families segregating schizophre-nia. Thirty-three families were identified through the NIMH Genetics Initiative that met the followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 27 publications
3
16
0
1
Order By: Relevance
“…In our sample of 38 Chinese schizophrenic families, preliminary analysis showed that the mean AAO in the offspring generation was significantly lower than that in the parental generation ( P < 0.001). This finding is in agreement with those of previous studies 5–13 . There was a medium difference in AAO of 11 years in previous reports, 15 and in the present study the difference is 8.8 years.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our sample of 38 Chinese schizophrenic families, preliminary analysis showed that the mean AAO in the offspring generation was significantly lower than that in the parental generation ( P < 0.001). This finding is in agreement with those of previous studies 5–13 . There was a medium difference in AAO of 11 years in previous reports, 15 and in the present study the difference is 8.8 years.…”
Section: Discussionsupporting
confidence: 94%
“…In families with schizophrenia, reduced penetrance and variable expansion are commonly found. Recent studies demonstrate that the clinical phenomenon of anticipation is present in the inheritance of schizophrenic disorders 5–13 . These findings may implicate genes with expanding trinucleotide repeat sequences in the genetic etiology of schizophrenia.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…[9][10][11][12] Additionally, intergenerational lengthening of the hSKCa3 CAG repeat may contribute to the phenomenon of 'anticipation' (increase in severity and decrease in age of onset in successive generations) that has been described for these disorders. 27 In order to help clarify the complex genetic basis of these neuropsychiatric diseases, we have embarked on case-control studies as a first test of the candidate role for hSKCa3. We have used two Caucasian populations which have previously been used in published studies.…”
mentioning
confidence: 99%
“…Several researchers who have minimized ascertainment biases and overcome methodological problems such as cohort effect and bilineality, have demonstrated a decrease in AO and an increase in severity in lower generations of schizophrenia patients, (Bassett and Honer 1994;Stöber et al 1995;Thibaut et al 1995;Gorwood et al 1996;Johnson et al 1997). On the other hand, doubts have been cast on data which showed anticipation in schizophrenia (Asherson et al 1994;Yaw et al 1996) and other familial disorders (Heiman et al 1996;Fraser 1997).…”
Section: Introductionmentioning
confidence: 99%